Eerste foto van Presser om 13.04 uur genomen. Sluitertijd 8 sec. diafragma 12,5. Twee afdrukken - Presser, Sem,
Eerste foto van Presser om 13.04 uur genomen. Sluitertijd 8 sec. diafragma 12,5. Twee afdrukken.